Exchange rate flexibility and the international liquidity “problem” - G. Zis (Intereconomics, 1983)
Contrary to the expectations of those who advocated flexible exchange rates prior to 1973, Williamson, in his study on exchange rate flexibility and reserve use, presented data which suggested “the paradoxical conclusion that reserve use actually increased following the adoption of floating”. As this finding was based on developments immediately after the final collapse of the Bretton Woods system in March 1973, there arises the question of whether it remains consistent with subsequent experience. Our author argues that the international liquidity “problem” has indeed not been resolved during the last decade and, proceeding from this conclusion, assesses its current implications.
Keywords: 330; Monetary Policy